Unveiling the Determinants of Financial Satisfaction among Civil Servants in Indonesia - Fifin Andhiana; Nadia Asandimitra Haryono; Ulil Hartono (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2024)
This study aims to ascertain the determinants of financial satisfaction among the state civil apparatus in Indonesia, including financial literacy and income. This study also examines the role of financial behavior in mediating the relationship between variables. This present study used a quantitative method with structural equation modeling. A Likert scale was used as the measurement in the quantitative research approach. The data were retrieved from 106 samples of the state civil apparatus in a certain area in Indonesia. The findings indicate that income can predict financial behavior and financial satisfaction. In addition, financial literacy is also recognized as prominent in predicting financial behavior and financial satisfaction. This study also confirms the role of financial behavior in mediating the linkage between financial literacy and financial satisfaction as well as the relationship between income and financial satisfaction. The findings offer implications for the government to manage financial literacy through various programs as its great role for financial satisfaction. Keywords: financial literacy, income, financial behavior, financial satisfaction